KOMUNIKASI INTERPESONAL KARYAWAN DIVISI OPERASIONAL PT FORMOSA SEJATI LOGISTICS SURABAYA DALAM MENJAGA HUBUNGAN BAIK DENGAN PELANGGAN - Mochamad Brilian Eky Fernanda; Bagus Cahyo Shah Adhi Pradana (Sintesa, 2026)
This study aims to analyze the interpersonal communication practices of operational division employees at PT Formosa Sejati Logistics Surabaya in maintaining good relationships with customers. This research is motivated by the high intensity of interaction between operational employees and customers in logistics service processes, including administrative activities, operational coordination, and the handling of field-related issues, which may lead to misunderstandings, conflicts, and customer dissatisfaction if not managed through effective interpersonal communication. This study employs a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, direct observation, and documentation involving operational division employees and customers of PT Formosa Sejati Logistics Surabaya. The analysis is based on the concept of interpersonal communication, which includes openness, empathy, supportiveness, positiveness, and equality, and is further examined through the lens of the Fundamental Interpersonal Relations Orientation (FIRO) theory, which encompasses the needs for inclusion, control, and affection. The findings indicate that the interpersonal communication practices implemented by operational employees are able to create effective and constructive interactions with customers through clear and honest information delivery, the ability to understand customer problems, and professional as well as equal treatment in service provision. These communication practices are proven to fulfill customers’ interpersonal needs in terms of inclusion, control, and affection, resulting in customers feeling accepted, valued, and trusted throughout the service process. The fulfillment of these interpersonal needs contributes to the development of trust, comfort, and customer loyalty, which ultimately strengthens long-term cooperative relationships between the company and its customers. This study emphasizes that interpersonal communication functions not only as a medium for conveying technical information but also as an essential relational strategy for improving service quality and sustaining business relationships within the logistics service sector.Keywords: Interpersonal Communication; Logistics Service; Customer Relations; Interpersonal Needs.